Anesthesia monitoring device development - Rahman, Tasneem; Suchi, Khadija Akhter (Computer Science and Engineering, BRAC University, 2011)
This thesis report is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Computer Science and Engineering, 2005.